Analysis of trampoline competition scores focusing on flight time - Yokozawa, T.; Kawano, Y.; Imawaka, T. (Journal of High Performance Sport, 2024)
Although flight time is an important factor in trampoline competitions, the relationship between flight time and competition scores has not been clarified. The purpose of this study was to clarify the factors associated with a high total score in trampoline competitions, with an especial focus on flight time. Data from national competitions of elite athletes (men: 207 trials, women: 187 trials) were included in the study. The flight time for each jump, including the time just before the first skill (T0), was obtained from the official competition system. T-score assumed from the elements of routine in each trial was simulated by an optimization approach that estimated the mechanical work for each skill to minimize the error in flight time. The difference in actual T-score relative to the simulated T-score was defined as U+03B4T. The relationships of T0 and T to scores were analyzed by multiple regression analysis. There was a significant positive correlation between each score and the total score for both men and women, with particularly large correlation coefficients for the E-score and T-score in men, and the D-score in women. T0 and U+03B4T alone contributed more than 50% of the total score (excluding penalty and point deductions due to landings) for both men and women, with U+03B4T making a particularly large contribution. For both men and women, T0 and U+03B4T positively contributed to the D-score and T-score. Additionally, U+03B4T was larger with smaller decreases in the flight time in the first half of the elements. These results indicated that T0 and U+03B4T contributed largely to the total score through the D-score and T-score. The large contribution of U+03B4T to the total score suggests the importance of maintaining flight time by obtaining a large reaction force during take-off in the first half of the elements.